A Hybrid Common Fixed Point Theorem under Certain Recent Properties. (23rd January 2014) - Kadelburg, Zoran; Chauhan, Sunny; Imdad, Mohammad
Abstract : We prove a common fixed point theorem for a hybrid pair of occasionally coincidentally idempotent mappings via common limit range property. Our result improves some results from the existing literature, especially the ones contained in Sintunavarat and Kumam (2009). Some illustrative and interesting examples to highlight the realized improvements are also furnished.